(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Taking advantage of the temporal dimension open to the question about theory, this study started from the temporality of the scenic event as a critical power. Taking into account that theory, like the scene, begins with a look, views were sought from philosophy to performance, through dramatic theater and stage interventions, which have served as a guide in this search. These views are analyzed as operations in time around a constellation of terms such as caesura, superposition, coexistence, breath, unfolding, crossing or metamorphosis, presented here as conditions for a theory to come.